Assessment of the impacts of climate change on drought intensity and frequency using SPI and SPEI in the Southern Pre-Balkash region, Kazakhstan - Alimkulov Sayat; Makhmudova Lyazzat; Talipova Elmira; Baspakova Gaukhar; Monkayeva Gulsara (Watershed Ecology and the Environment)
This paper presents a study of droughts in the South Pre-Balkash region that considers climate change and its impact on the intensity and frequency of drought periods. The main objective of this study is to assess changes in climatic parameters and their impact on the development of droughts using standardized precipitation indices (SPI) and precipitation evapotranspiration (SPEI) for the period 1950–2023. Long-term rainfall and temperature data and remote sensing data from the Google Earth Engine platform were used for the analysis. The Mann-Kendall test was applied to assess trends in climatic conditions and drought characteristics.The results showed that although both the SPI and SPEI can be used to assess droughts, the SPEI is more effective at capturing changes in air temperature increases. The intensity and frequency of drought periods increased after the 1990 s, especially as measured by the SPEI. Additionally, the results of the present study indicate an increase in the intensity and frequency of dry periods, which is associated with climate change. In the study area, climate change is characterised mainly by an increase in air temperature (0.17–0.39 °C/10 years). The SPEI index is more sensitive to changes in the water balance, as it takes into account the influences of both precipitation and evaporation, in contrast to the SPI index, which considers only the influence of precipitation. Consequently, when drought conditions are analyzed using the SPEI index, a more accurate representation of the depth and severity of drought is obtained. These findings have important implications for the development of adaptation measures in agriculture and water management in the context of increasing drought risk in the Southern Pre-Balkash region.